Crystallization of bothropstoxin II isolated from the venom of Bothrops jararacussu - Bortoleto, R. K.; Ward, R. J.; Giglio, JR; Cintra, ACO; Arni, R. K. (Elsevier B.V., 1996)
A myotoxic phospholipase A(2), bothropstoxin II, which exhibits low hydrolytic activity, was crystallized and X-ray diffraction data were collected to a resolution of 2.2 Angstrom. Preliminary analysis reveals the presence of three molecules in the asymmetric unit. Copyright (C) 1996 Elsevier B.V. Ltd.